Rate Coefficients of C1 and C2 Criegee Intermediate Reactions with Formic and Acetic Acid Near the Collision Limit: Direct Kinetics Measurements and Atmospheric Implications** - Welz, Oliver (Angew Chem Int Ed Engl, 2014)
Rate coefficients are directly determined for the reactions of the Criegee intermediates (CI) CH(2)OO and CH(3)CHOO with the two simplest carboxylic acids, formic acid (HCOOH) and acetic acid (CH(3)COOH), employing two complementary techniques: multiplexed photoionization mass spectrometry and cavity-enhanced broadband ultraviolet absorption spectroscopy. The measured rate coefficients are in excess of 1×10(−10) cm(3) s(−1), several orders of magnitude larger than those suggested from many previous alkene ozonolysis experiments and assumed in atmospheric modeling studies. These results suggest that the reaction with carboxylic acids is a substantially more important loss process for CIs than is presently assumed. Implementing these rate coefficients in global atmospheric models shows that reactions between CI and organic acids make a substantial contribution to removal of these acids in terrestrial equatorial areas and in other regions where high CI concentrations occur such as high northern latitudes, and implies that sources of acids in these areas are larger than previously recognized.